Sexual behaviours among dyadic vehicle occupants. (February 2022) - Newton, James David Albert; Demant, Daniel; Phillips, James G.; Struckman-Johnson, Cindy; Oviedo-Trespalacios, Oscar
Highlights: Content analysis was applied to sexually explicit media depicting sex while driving. Videos depicting dyads (driver and passenger) in a moving vehicle were sourced from Pornhub.com. Sexual activities were investigated by gender and role in the vehicle. The driver was generally male and the receiver of the sexual activity. Abstract: Sexual activity while driving is a risky behaviour frequently found across media. However, much is unknown about the practices and roles that dyadic occupants of vehicles (i.e. a driver and passenger) perform when engaging in sexual activity while driving. To cover this gap, a content analysis of sexually explicit media (SEM) was conducted on a sample of 208 videos taken from Pornhub.com. The videos portrayed a naturalistic driving situation of a driver of a moving vehicle engaging in sexual activity with a passenger. Videos were coded for sexual behaviours and characteristics of the vehicle occupants (gender and role). Drivers were generally male, while passengers were female. A range of sexual activities while driving were coded, including oral sex, unclothed and clothed masturbation, varying levels of nudity, and ejaculation. Drivers appear to be the focus of sexual attention, as they are generally the ones receiving sexual acts from the passenger, and predominantly ejaculating. Additionally, female passengers perform oral sex on drivers more often than male passengers, and female vehicle occupants tend to have greater levels of nudist exposure than males. This study highlights the complexities of sexual activity while driving and patterns for consideration when developing interventions.